2018
DOI: 10.3233/jad-170474
|View full text |Cite
|
Sign up to set email alerts
|

GDF11 Rejuvenates Cerebrovascular Structure and Function in an Animal Model of Alzheimer’s Disease

Abstract: Cerebral amyloid angiopathy (CAA) is present in up to 90% of patients with Alzheimer's disease (AD), and may interact with classical neuropathology to exacerbate cognitive decline. Since growth differentiation factor 11 (GDF11) can activate vascular remodeling, we tested its effects on cognitive function and neuroinflammatory changes of AD model mice. We intravenously administered GDF11 or vehicle daily to 12-month-old transgenic mice overexpressing the amyloid-β protein precursor (AβPP)/PS1). Cognitive functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 48 publications
2
23
0
Order By: Relevance
“…Whether GDF11-treated old mice exhibit improved cognition through olfactory discrimination tasks and/or hippocampus-dependent spatial navigation tasks also needs further research. Notably, recent studies have shown improved neurocognitive behavior in rodents treated with GDF11 in stroke 50 , 53 and AD 52 models. Therefore, it is feasible that systemic GDF11 treatment also could lead to enhanced cognition in aging.…”
Section: Discussionmentioning
confidence: 99%
“…Whether GDF11-treated old mice exhibit improved cognition through olfactory discrimination tasks and/or hippocampus-dependent spatial navigation tasks also needs further research. Notably, recent studies have shown improved neurocognitive behavior in rodents treated with GDF11 in stroke 50 , 53 and AD 52 models. Therefore, it is feasible that systemic GDF11 treatment also could lead to enhanced cognition in aging.…”
Section: Discussionmentioning
confidence: 99%
“…One study demonstrates that GDF11 reduces the mRNA levels of IL-6, IL-1␤, and TNF-␣ during atherosclerosis lesion formation in apoE Ϫ/Ϫ mice fed with high-fat diet, together with the protein levels of IL-6 and TNF-␣ (28). Another study reports that GDF11 inhibits the expression of the inflammatory markers Iba-1 and glial fibrillary acidic protein in the cerebral vasculature of Alzheimer's disease mice (46). In this study, we confirmed that GDF11 had Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that restoring systemic GDF11 level reversed age-related cardiac hypertrophy and brain dysfunction (20,23). Recently, studies have reported that both the levels of proinflammatory cytokines in apolipoprotein E-null mice and the neuroinflammatory changes in the brain parenchyma of Alzheimer's disease model mice significantly decreased after GDF11 treatment (28,46). Additionally, UC is a kind of inflammatory disease in the gastrointestinal tract, but there have been no reports on the role of GDF11 in the regulation of intestinal inflammation during UC.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, other reports argued that GDF11 was positively associated with aging, cachexia, and inhibition of muscle regeneration in aged mice (Egerman et al, ; Harper et al, ; Jones et al, ), while different studies showed a beneficial role for GDF11 in the periphery (Poggioli et al, ; Su et al, ; Walker et al, ). In the central nervous system, GDF11 was also shown to be neuroprotective for neurovascular recovery and neurogenesis (Anqi, Ruiqi, Yanming, & Chao, ; Ma et al, ; Ozek, Krolewski, Buchanan, & Rubin, ; Schafer & LeBrasseur, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%